Organisasi Perempuan sebagai Agen Sosialisasi Politik di Kabupaten Kudus (Studi Kasus: Fatayat dan Nasyiatul Aisyiyah) - Dewi, Nevy Rusmarina (State Islamic Institute of Kudus (IAIN Kudus), 2022)
The interest of women in Kudus in joining women's organizations is quite high, among these organizations are Fatayat and Nasyiatul Aisyiah (NA). Although participation in organizations is quite high, participation in political life is still not maximized. This can be seen in the absence of female legislative members and the absence of female regents in Kudus. This study discusses the role of women's organizations in Kudus, especially Fatayat and Nasyiatul Aisyiyah in carrying out political socialization for women in Kudus. The research method used is qualitative-descriptive. The results showed that Fatayat and Nasyiatul Aisyiyah were still less than optimal in conducting political socialization